2022
DOI: 10.1093/cercor/bhab505
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive changes in delay discounting in males during the COVID-19 pandemic: the predictive role of functional connectome

Abstract: The Coronavirus disease of 2019 (COVID-19) and measures to curb it created population-level changes in male-dominant impulsive and risky behaviors such as violent crimes and gambling. One possible explanation for this is that the pandemic has been stressful, and males, more so than females, tend to respond to stress by altering their focus on immediate versus delayed rewards, as reflected in their delay discounting rates. Delay discounting rates from healthy undergraduate students were collected twice during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Two studies have measured biological and physical changes related to the COVID-19 pandemic, and the results have demonstrated that those with worse health conditions exhibited more impulsive behaviors (Xiao et al ., 2022 ). Findings suggest that unvaccinated individuals display higher rates of delay discounting than vaccinated individuals (Halilova et al ., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies have measured biological and physical changes related to the COVID-19 pandemic, and the results have demonstrated that those with worse health conditions exhibited more impulsive behaviors (Xiao et al ., 2022 ). Findings suggest that unvaccinated individuals display higher rates of delay discounting than vaccinated individuals (Halilova et al ., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Xiao et al . ( 2022 ) measured individual differences in the brain functional connectivity network prior to the pandemic, and the results showed that consensus functional connectivity network strength declined in relation to the increase in delay discounting during the pandemic. As the frontal parietal network is unique to stress, it was found to be an essential factor influencing the stress brought by the pandemic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these tools are limited to subjective reporting, and thus more objective indicators are needed for evaluating educational leadership. Neuroscience has already demonstrated its ability to identify and even predict mental disorders, personality traits, and decision‐making ability (Gabrieli et al., 2015; Tong et al., 2022; Xiao et al., 2022). Therefore, it has great potential for practical assessment, providing stable and objective outputs for educational leadership.…”
Section: Neuroscience Applications In Educational Leadership Practicesmentioning
confidence: 99%
“…According to WHO, the adult population with obesity had exceeded those with normal weight in the world (World Health Organization, 2020). The COVID-19 and associated lockdown changed the way we live and communicate (Xiao et al, 2022), which may also promote obesity and associated metabolic diseases (Clemmensen et al, 2020). Anyhow, overweight and obesity was one of the top five factors affecting the disease risk (Kelley and Berridge, 2002;Rolls, 2007;Trinko et al, 2007;Volkow et al, 2008;Chen et al, 2018), which can impose a heavy burden the health system (He et al, 2014a(He et al, ,b, 2015Gao et al, 2020;Liu et al, 2022).…”
mentioning
confidence: 99%